c - 9; 9; Mass-Line Media Center (Dhaka, Bangladesh) (b, 2002)
Contributed articles on social perspectives of mass media and adequacy of press coverage in Bangladesh; edited papers of various seminars.
In Bengali.
Keywords: Mass media -- Social aspects -- Bangladesh; Bangladesh -- Press coverage